STRATEGI KEGIATAN EKSTRAKURIKULER DALAM MENINGKATKAN KINERJA TENTOR EKSTRAKURIKULER SAINS DI SMA NURIS JEMBER - Istifadah, Istifadah; Maghfiroh, Hikmatul; Firdaus, Anzili (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Students in developing the students' talents and interests. The aim of this research is to describe the process of planning, implementing and evaluating science extracurricular activities at the Nuris Jember Senior Secondary School. This research uses a qualitative approach and a case study type of research, using passive participant observation techniques, semi-structured interviews and documentation. Data analysis was carried out using data reduction, data display, conclusion and verification steps. Data validity is carried out by source triangulation and technical triangulation. First, the research results show that planning for science extracurricular activities is said to improve when determining targets and analyzing tutor positions. secondly, the implementation of science extracurricular activities increases when coaching tutors in terms of performance, discipline as well as providing awards and motivation to tutors. Third, the evaluation of science extracurricular activities used is the performance assessment which is held at the end of the month, semester and end of the year.